EFFECTIVENESS OF AVOCADO SEED EXTRACT (Persea americana Mill.) ON INHIBIT GROWTH OF Candida albicans AND Trichopyton sp. - Marsus, Ismat; Nur, Muhammad Khaerul; Fahruddin; Baharuddin, Suherman (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
In the world of medicine, avocados (Persea americane Mill.) are mostly used as traditional medicine in treating various diseases, but in the avocado seed it turns out that so far, it has only been left and thrown away, even though it contains secondary metabolite compounds that can be used as medicinal ingredients, including alkaloids, flavonoids, tannins, saponins, phenolics, terpenoids, and steroids. This study aimed to determine the effectiveness of an avocado seed extract (Persea americana Mill.) concentrations of 5% 10% and 15% b/v against the growth of Candida albicans and Trichopyton sp. and determine at what concentration is most effective. This research is experimental which is a laboratory study using the method of extraction by maceration and disc diffusion (Kirby-Bauer Test) in testffectiveness of avo (Persea americana Mill.) against the growth of Candida albicans and Trichopyton spto testlts obtained from the avocadoment of the diameter of the inhibition were analyzed by one-way analysis of variance (ANOVA) and correlation test using the IBM SPSS Statistics version 26 program. The results showed that avocado seed extract (Persea americana Mill) was effective in inhibiting the growth of Candida albicans and Trichopyton sp. The most effective concentration was at a concentration of 15% b/v, respectively, where the inhibition of Candida albicans was 11.84 ± 0.238 mm while the inhibition of Trichopyton sp. was 12.58 ± 0.005 mm (oneway Anova, ? = 0.05) Keywords: Effectiveness, Persea americana Mill, Candida albicans, Trichopyton sp., Kirby- Bauer